The Queensland Baptist 1923-1931. - Baptist Association of Queensland; Archive CD Books Australia ([Modbury, S. Aust.] : Archive CD Books Australia, 2008)
"Each issue contains articles on issues of the day, topical articles by different people, news from Baptist churches throughout the state of Queensland, missionary news, and inter-colonial news. They also often contain reports and statistics of different kinds, articles on different people, obituaries and articles on different Queensland churches as well as stories, poems, songs and letters. They even include adverts of local businesses (i.e.. bookshops, dentists, confectioner, organ seller, insurance, and clothing stores)"
Title from label.
CD-ROM.
Electronic version of print publication.
System requirements: Adobe Acrobat Reader 6 or later
Keywords: Baptist Association of Queensland; Baptists -- Queensland